Brain Drain and Gender Inequality in Turkey - Elveren, Adem Yavuz (Springer International Publishing, 2018)
This book provides a comprehensive analysis of the brain drain from Turkey, with particular focus on its gender dimension. The author presents a review of brain drain literature, as well as analyzing the brain drain from Turkey using original survey data. Presenting an account of state changes in Turkey, and using a range of empirical methods, the book argues that women have a higher tendency not to return to the country due to increasing gender inequality, borne out of a shift towards a more authoritarian regime over the last decade. Brain Drain and Gender Inequality in Turkey will be of interest to students and scholars across a range of disciplines, including migration studies, social policy, and gender studies.